1993
DOI: 10.1152/jappl.1993.74.6.2704
|View full text |Cite
|
Sign up to set email alerts
|

Surface electromyogram power spectrum in human quadriceps muscle during incremental exercise

Abstract: Spectral electromyographic (EMG) changes in human quadriceps muscles were studied to reinvestigate discrepant results concerning mean power frequency (MPF) changes during dynamic exercise. An incremental test consisting of a quasi-linear increase in mechanical power on a bicycle ergometer (for 20-100% of maximal aerobic power) was performed by forty subjects. During this test, surface EMGs from the quadriceps muscles showed that EMG total power (PEMG) increased with a curvilinear pattern for every subject, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
33
0
3

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 0 publications
7
33
0
3
Order By: Relevance
“…Present findings concerning the relationship between changes in f med and blood lactate concentration in dynamic exercise are in agreement with Gamet et al (1993). They have studied changes in MPF in human quadriceps muscle in 40 subjects.…”
Section: Discussionsupporting
confidence: 85%
“…Present findings concerning the relationship between changes in f med and blood lactate concentration in dynamic exercise are in agreement with Gamet et al (1993). They have studied changes in MPF in human quadriceps muscle in 40 subjects.…”
Section: Discussionsupporting
confidence: 85%
“…Increased MF value during suprathreshold exercise and its persistence for 10 min during the recovery period where [LA] = 4.0 ± 0.3 mmol/L (vs. 2.0 ± 0.3 mmol/L after subthreshold exercise) cannot be explained by the changes in M wave, which should increase and not decrease the low-frequency FFT component. 1 As already shown, 2,6 no EMG signs of ''central'' muscle fatigue, i.e., decreased MF value, were found in the two situations. Increased MF value may result from the enhanced recruitment of the smaller motor units and/or an overall increase in the firing rate of all motor units.…”
Section: Discussionmentioning
confidence: 61%
“…4,7,9,11 Some studies 4,9 reported a decrease in mean spectral frequency (MF), not confirmed by others. 7,11 The neuromuscular transmission and the sarcolemmal excitability do not appear to be altered during sustained maximal voluntary contraction 2 and M-wave changes during dynamic exercise are not documented. Data on correlative changes in SEMG and muscle metabolism are also rather sparse.…”
mentioning
confidence: 95%